Comparative Analysis of Nuclear (Ef1?) and Mitochondrial (mt-CO1 and mt-Nad5) Markers for Molecular Characterization of Sheep Isolates of Echinococcus granulosus sensu lato - Kilinc, Seyma Gunyakti; Kesik, Harun Kaya; Celik, Figen; Simsek, Sami (Wiley, 2025)
BackgroundEchinococcus granulosus is a zoonotic disease that is widespread worldwide.ObjectiveThis study aimed to determine the genetic diversity of E. granulosus isolates in sheep. Partial mitochondrial and nuclear gene sequences were used to determine intraspecific variation.MethodsFor this purpose, 41 sheep hydatid cyst isolates were collected from slaughterhouses in Elazig and Bingol provinces of T & uuml;rkiye. Following genomic DNA isolation from the germinal membrane of the cysts, PCR amplification and subsequent DNA sequence analysis were performed using primers that amplify mitochondrial CO1, Nad5, and nuclear ef1 alpha gene regions.ResultsDNA sequence analyses of mt-CO1 (1603 bp) and mt-Nad5 (625 bp) gene regions showed that 39 out of 41 isolates were identified as G1 and two isolates as G3. When the phylogenies formed by the sequences belonging to different gene regions were evaluated; in the phylogenetic tree created with the mt-CO1 and Nad5 gene dataset, G1 and G3 isolates were in separate clades with the reference sequences, while in the phylogenetic tree created with the nuclear gene region ef1 alpha dataset, the isolate belonging to the G3 genotype (ef1a.01) formed a sister clade with the G1 genotypes and the reference sequence. According to the haplotype network results obtained, 14 haplotypes, 15 haplotypes, and two haplotypes were determined for mt-CO1, mt-Nad5, and ef1 alpha gene regions, respectively. Haplotype analysis of mt-CO1 and mt-Nad5 gene regions revealed high haplotype and low nucleotide diversity. Low nucleotide diversity was detected, and two haplotypes were determined as a result of haplotype analysis ef1 alpha (1343 bp) gene.
Keywords: ef1 alpha; E. granulosus s.s. (G1/G3); haplotype; sheep; mt-CO1; mt-Nad5